PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN DISPOSISI MATEMATIS SISWA SMP - Ade Sriwahyuni; Jajang Rahmatudin; Rifqi Hidayat (Integral : Pendidikan Matematika, 2018)
This research is motivated by the low ability of students 'mathematical literacy and dispositionin learning mathematics, and the need for the use of learning models that can improvestudents' mathematical abilities. This research is a quasi-experimental study. The researchdesign used is Nonequivalent Control Group Design and Purposive Sampling samplingtechnique. The population is grade VIII SMPN 2 Sedong, Cirebon Regency, Academic Year2018/2019. The research sample involved eighth grade students, namely 32 students of classVIII B as an experimental class and 32 students of class VIII A as a control class. Based on theresults of the study, show that: (1) the literacy ability of students who learn using PBL modelsis better than students who use conventional learning; (2) Improvement of students'mathematical literacy skills whose learning uses PBL models is better than students who learnconventionally; (3) The ability of mathematical disposition of students whose learning usesPBL models is better than students who learn conventionally; and (4) Improving students'mathematical disposition abilities using the PBL model is better than students who learnconventionally.Keywords: PBL, Literacy Ability, Mathematical Disposition